Postmortem findings in Ontario racehorses, 2003–2015. (July 2017) - DeLay, Josepha
Postmortem lesions and cause of death were evaluated retrospectively for 963 horses examined as part of the Ontario Racing Commission Death Registry over a 13-y period. The Death Registry was established in 2003 to identify factors leading to death or euthanasia of racehorses in this Canadian province. Postmortem examination was carried out on 56% of horses reported to the Death Registry and included Standardbred, Thoroughbred, and American Quarter Horses. Musculoskeletal injury was the most common reason for death associated with racing or training among all racehorses and involved 68% of horses. A history of sudden death during or immediately following exercise was described for 31% of racing- or training-associated deaths, and in 16% of all horses in the study. Sudden death occurred in horses of all breeds, and our report describes lesions associated with sudden death in a series of Standardbreds. The cause of death in these cases was most frequently attributed to cardiopulmonary lesions. The cause of death was undetermined in 20% of sudden death cases, and it is speculated that cardiac arrhythmia may have contributed to these deaths. Injection-associated death was documented in 4% of the study population. Lesions among horses whose death was not associated with exercise were similar to those in other equine populations, and lesions involving the gastrointestinal system were most common. Standardization of pathology reporting of pulmonary and other lesions in racehorse postmortem cases would allow direct comparison of results among racehorse populations.